2021
DOI: 10.58397/ashkmdc.v26i1.346
|View full text |Cite
|
Sign up to set email alerts
|

The psychological impact of COVID-19 among the undergraduate dentistry students of Sindh and Baluchistan and how they manage it.

Abstract: Objective: The purpose of the current study was to evaluate the anxiety among the undergraduate dentistry students during the COVID-19 pandemic. It also aimed to find out their stress management strategies. Methods: A total of 809 undergraduate dentistry students of Sindh and Balochistan contributed to this web-based cross-sectional study. A validated e-questionnaire created using Google form were distributed among the dental college student through social media. Spss 22 was used for statistical analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…According to the current study, fear is prevalent among dentistry students. Previous studies have reported that the contagious nature of the virus, disruption in studies, especially the online classes, exposure with the suspected patients, and the impact of COVID-19 on dentistry are the factors responsible for fear (12,23). The findings of another study conducted in Pakistan targeting the health care professionals also mentioned that the anxiety of a family member to getting an infection is high compared to oneself, according to the current study's findings (9).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…According to the current study, fear is prevalent among dentistry students. Previous studies have reported that the contagious nature of the virus, disruption in studies, especially the online classes, exposure with the suspected patients, and the impact of COVID-19 on dentistry are the factors responsible for fear (12,23). The findings of another study conducted in Pakistan targeting the health care professionals also mentioned that the anxiety of a family member to getting an infection is high compared to oneself, according to the current study's findings (9).…”
Section: Discussionsupporting
confidence: 63%
“…Children and older peopleisolated from their friends and, in some cases, their families, which influences their mental and physical well-being (10). Several studies have reported the psychological impact of pandemics on the general public, patients and their families, doctors, medical staff, or other healthcare professionals (11)(12)(13)(14)(15). With the increase in the discovery of different genetic variants of the virus, the current pandemic is nowhere near its end.…”
Section: Introductionmentioning
confidence: 99%